Divergent motor projections from the pedunculopontine nucleus are differentially regulated in Parkinsonism - Martinez-Gonzalez, Cristina (Springer Berlin Heidelberg, 2013)
The pedunculopontine nucleus (PPN) is composed of neurons with different connectivity patterns that express different neurochemical markers, display distinct firing characteristics and are topographically organized in functional domains across its rostro-caudal axis. Previous reports have shown that the caudal region of the PPN is interconnected with motor regions of both the basal ganglia and brainstem/medulla. The co-distribution of ascending and descending motor outputs raises the question as to whether the PPN provides a coordinated or differential modulation of its targets in the basal ganglia and the medulla. To address this, we retrogradely labeled neurons in the two main PPN pathways involved in motor control and determined whether they project to one or both structures, their neurochemical phenotype, and their activity in normal and dopamine depleted rats, as indicated by Egr-1 expression. We show that ascending and descending motor pathways from the PPN arise largely from separate neurons that intermingle in the same region of the PPN, but have a distinct neurochemical composition and are differentially regulated in the Parkinsonian state. Thus, neurons projecting to the subthalamic nucleus consist of cholinergic, calbindin- and calretinin-expressing neurons, and Egr-1 is upregulated following a 6-hydroxydopamine lesion. In contrast, a larger proportion of neurons projecting to the gigantocellular nucleus are cholinergic, none express calbindin and the expression of Egr-1 is not changed by the dopamine lesion. Our results suggest that ascending and descending motor connections of the PPN are largely mediated by different sets of neurons and there are cell type-specific changes in Parkinsonian rats.